2021
DOI: 10.1007/s13659-021-00319-8
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Research on Chemical Constituents and Their Biological Activities of the Genus Actinidia

Abstract: Kiwi, a fruit from plants of the genus Actinidia, is one of the famous fruits with thousand years of edible history. In the past twenty years, a great deal of research has been done on the chemical constituents of the Actinidia species. A large number of secondary metabolites including triterpenoids, flavonoids, phenols, etc. have been identified from differents parts of Actinidia plants, which exhibited significant in vitro and in vivo pharmacological activities including anticancer, anti-inflammatory, neurop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 140 publications
(287 reference statements)
0
6
0
Order By: Relevance
“…Maslinic acid is a pentacyclic triterpene with antioxidant and cardioprotective effects, and it is capable of reducing the oxidative damage caused by UVB radiation in HFF-1 cells [ 68 ] and inhibiting the activation of NF-kB pathways in Sprague-Dawley rats [ 69 ]. Actinidic acid was first isolated from unripe kiwi fruit peel [ 70 ], and studies have shown that its derivatives exert antidiabetic effects by inhibiting the activity of α-glucosidase [ 71 ] and pancreatic lipase [ 72 ]. Luteolin-4-glucoside is a flavonoid showing good antioxidant and antiproliferative capacities [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…Maslinic acid is a pentacyclic triterpene with antioxidant and cardioprotective effects, and it is capable of reducing the oxidative damage caused by UVB radiation in HFF-1 cells [ 68 ] and inhibiting the activation of NF-kB pathways in Sprague-Dawley rats [ 69 ]. Actinidic acid was first isolated from unripe kiwi fruit peel [ 70 ], and studies have shown that its derivatives exert antidiabetic effects by inhibiting the activity of α-glucosidase [ 71 ] and pancreatic lipase [ 72 ]. Luteolin-4-glucoside is a flavonoid showing good antioxidant and antiproliferative capacities [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…Generally, DM treatment is achieved by conventional drugs which act mainly by stimulating insulin absorption and its release from the pancreas or by inhibiting carbohydrate-degrading enzymes 4 . The incessant development in natural product research catalysed extensive studies of numerous plant species for their pharmacological roles 5 . In the Philippines alone, there is remarkably rich flora with approximately 10,000 different species 6 and over the years, medicinal plants have been used for the discovery of novel treatments either in the form of pure compounds or crude extracts 7 .…”
Section: Introductionmentioning
confidence: 99%
“…22 Recently, the anti-tumor effects of OA with anti-bacterial, antiinflammatory, anti-ulcer effects and neuroprotective effects have been steadily accepted. [23][24][25] However, the poor water-solubility of OA limits its bioavailability and therefore it shows limited therapeutic efficacy in tumor treatment in conventional administration approaches. Taking these into consideration, liposomes were used to encapsulate OA to improve the bioavailability of OA in this study (Scheme 1A).…”
Section: Introductionmentioning
confidence: 99%